2019
DOI: 10.7440/histcrit74.2019.02
|View full text |Cite
|
Sign up to set email alerts
|

Tras la pista de “terribles veranos” y “copiosas lluvias”. Elementos para una historia climática del territorio colombiano

Abstract: Objective/Context: The objective of this article is to aid historians who are interested in recovering the climate history of the current Colombian territory, in their explanations and research about climate and weather factors. Methodology: In order to face the lack of quantitative records, this paper shows some alternatives such as looking for signs from indirect sources, the contrast of sources, series-making, and detection of teleconnections. Originality: It shows the potential of documentary sources, it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Nevertheless, other regions and countries have seen rapid growth, such as southeastern Europe (Botić, 2020; Cheval et al, 2020; Kužić, 2020; Mrgić & Dražeta, 2020; Pašić et al, 2020; Perșoiu & Perșoiu, 2018) and Ireland (Kelly, 2020; Kelly & O'Carragáin, 2021; Sweeney, 2020). Significant new work on climate and history has also continued for Latin America (e.g., Mora Pacheco, 2019) and Africa (e.g., Klein et al, 2018), as well as parts of Asia that had received little coverage until the past five years (Adamson & Nash, 2018b): Korea (Jun & Sethi, 2021), Singapore and Malaysia (Williamson, 2021), and the Middle East (Fleitmann et al, 2022; Meklach et al, 2021; Pehlivan, 2020). Since 2021, for example, studies combining historical research with speleothem and tree‐ring data have demonstrated the impact of a previously unknown drought on crises in Safavid Iran and Ottoman Iraq at the end of the 17th century—regions almost completely lacking in climate history research just a decade before (Gustafson & Speer, 2022; Husain, 2021).…”
Section: Recent Directions In Researchmentioning
confidence: 99%
“…Nevertheless, other regions and countries have seen rapid growth, such as southeastern Europe (Botić, 2020; Cheval et al, 2020; Kužić, 2020; Mrgić & Dražeta, 2020; Pašić et al, 2020; Perșoiu & Perșoiu, 2018) and Ireland (Kelly, 2020; Kelly & O'Carragáin, 2021; Sweeney, 2020). Significant new work on climate and history has also continued for Latin America (e.g., Mora Pacheco, 2019) and Africa (e.g., Klein et al, 2018), as well as parts of Asia that had received little coverage until the past five years (Adamson & Nash, 2018b): Korea (Jun & Sethi, 2021), Singapore and Malaysia (Williamson, 2021), and the Middle East (Fleitmann et al, 2022; Meklach et al, 2021; Pehlivan, 2020). Since 2021, for example, studies combining historical research with speleothem and tree‐ring data have demonstrated the impact of a previously unknown drought on crises in Safavid Iran and Ottoman Iraq at the end of the 17th century—regions almost completely lacking in climate history research just a decade before (Gustafson & Speer, 2022; Husain, 2021).…”
Section: Recent Directions In Researchmentioning
confidence: 99%